On the shoulders of giants (part two): an inspirational woman - Keith White (Scottish Journal of Residential Child Care)
This is the second paper based on the keynote speech given by Keith White at the SIRCC conference on 7th June 2007. In the first paper (White, 2007) he identified a few of the historically significant figures in residential child care and discussed the life and work of Janusz Korczak. This paper will focus on the life of Pandita Ramabai, an extraordinary woman who lived an extraordinary life in extraordinary times.